1998
DOI: 10.1007/s002800050817
|View full text |Cite
|
Sign up to set email alerts
|

The benzoquinone ansamycin 17-allylamino-17-demethoxygeldanamycin binds to HSP90 and shares important biologic activities with geldanamycin

Abstract: 17-AG shares the important biologic features of its parent compound GA. Since 17-AG has a better toxicity profile than GA, it is an interesting candidate benzoquinone ansamycin for clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
271
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(278 citation statements)
references
References 28 publications
4
271
0
3
Order By: Relevance
“…Chemicals that may reduce the efflux rates of iodine, such as lithium [23], DIDS, and tanespimycin [9,10] have also been recognized; however, the mechanisms relevant to such activities have not yet characterized in detail. Tanespimycin, a less liver toxic and more stable geldanamycin derivative [24] has been previously identified as a chemotherapeutic agent. MicroPET images showed that 4 h or 24 h of tanespimycin treatment induced significant reductions in tumor size in PC-3 tumor-bearing nude mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals that may reduce the efflux rates of iodine, such as lithium [23], DIDS, and tanespimycin [9,10] have also been recognized; however, the mechanisms relevant to such activities have not yet characterized in detail. Tanespimycin, a less liver toxic and more stable geldanamycin derivative [24] has been previously identified as a chemotherapeutic agent. MicroPET images showed that 4 h or 24 h of tanespimycin treatment induced significant reductions in tumor size in PC-3 tumor-bearing nude mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…These were selected as they are tumor types in which clinical activity has been reported with 17-AAG (46,54). Like 17-AAG (15,55) and CCT018159 (27), depletion of well-established HSP90 client proteins, such as ERBB2, cyclin-dependent kinase 4, and C-RAF, was observed. ERBB2 was consistently the most sensitive client.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies focused around these naturally occurring compounds, producing geldanamycin derivatives (such as 17-allyamino-geldanamycin; ref. 37), or synthesizing new compounds with similar binding capacity (e.g., CCT018159; ref. 38).…”
Section: Discussionmentioning
confidence: 99%